2000
DOI: 10.1074/jbc.m002284200
|View full text |Cite
|
Sign up to set email alerts
|

Production of Recombinant Human Type I Procollagen Trimers Using a Four-gene Expression System in the Yeast Saccharomyces cerevisiae

Abstract: The expression of stable recombinant human collagen requires an expression system capable of post-translational modifications and assembly of the procollagen polypeptides. Two genes were expressed in the yeast Saccharomyces cerevisiae to produce both propeptide chains that constitute human type I procollagen. Two additional genes were expressed coding for the subunits of prolyl hydroxylase, an enzyme that post-translationally modifies procollagen and that confers heat (thermal) stability to the triple helical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 41 publications
5
74
1
2
Order By: Relevance
“…72 Yeast systems are a particularly good choice for recombinant human collagen production because they can be engineered to hydroxylate prolines and can yield high expression levels of collagen. Prior studies have shown that P. pastoris 55,73,74 and S. cereVisiae 28,39,75 can produce hydroxylated human collagen types I, II, and III. 39,55,73,76 In fact, commercially available recombinant human collagen III uses a P. pastoris expression system 77 based on cDNA.…”
Section: Discussionmentioning
confidence: 99%
“…72 Yeast systems are a particularly good choice for recombinant human collagen production because they can be engineered to hydroxylate prolines and can yield high expression levels of collagen. Prior studies have shown that P. pastoris 55,73,74 and S. cereVisiae 28,39,75 can produce hydroxylated human collagen types I, II, and III. 39,55,73,76 In fact, commercially available recombinant human collagen III uses a P. pastoris expression system 77 based on cDNA.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several groups have reported the successful production of hydroxylated collagen using Saccharomyces systems (33)(34)(35). This can be achieved, for example, by using non-integrating, stable vectors.…”
Section: Collagen As a Biomaterialsmentioning
confidence: 99%
“…Other arrangements of the 3 genes on these vectors are also effective (36). Alternatively, the 3 genes can be introduced as multiple copies integrated into the yeast genome, all under the control of GAL promoters (35). This approach leads to excellent yields of collagen that has a high degree of prolyl hydroxylation, as shown by a stability (melting temperature) comparable to native, tissue derived collagen (35).…”
Section: Collagen As a Biomaterialsmentioning
confidence: 99%
“…Notable progress has been made on commercial, recombinant production of human collagens. 7,[10][11][12][13][14][15][16][17] However, the rapidly emerging technologies that have characterized and produced recombinant non-animal (bacterial) collagens in E. coli [23][24][25]27,28 have introduced an exciting new collagen option that can be readily customized for specific biomedical applications. 28,33 These customized collagens will pave the way for more diverse applications in medical devices, implantable materials and potentially as scaffolds for stem cells, to name but a few examples of uses for these recombinant bacterial collagens.…”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
“…7 On the other hand, yeast systems were considerably more promising, and several have been used successfully for the expression of full-length hydroxylated human collagens ( Table 1). [10][11][12] The advantage of the yeasts is they can be optimized to integrate and co-express 3 or 4 genes concurrently. The most successful application, which has provided commercial opportunities, has emerged from expression in P. pastoris ( Table 1).…”
mentioning
confidence: 99%